PENGARUH PERTUMBUHAN PERUSAHAANDAN RISIKO PERUSAHAANTERHADAP PENGUNGKAPAN INTERNET FINANCIAL REPORTING (IFR) - M. Riduan Abdillah (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2016)
Abstract, This research aimed to analyze the effect of the growth of the companyand the company's risk on the disclosure of Internet Financial Reporting (IFR). The population of this research is all manufacturing companies listed in Indonesia Stock Exchange in 2013. The research sample selection using purposive sampling method, the number of samples in this study as many as 102 companies. Research hypothesis testing using multiple regression analysis through the Smart PLS 2.0 M3. The results of hypothesis testing found evidence that the growth of the company and the company's risk did not significantly affect the disclosure of Internet Financial Reporting (IFR).